Thinking teams, thinking clients : knowledge-based teamwork - Opie, Anne (Columbia University Press, 2000)
A universal method of working with teams that focuses on working with knowledge and is applicable to a variety of disciplines. Drawing on Foucaultian theories of discourse, Thinking Teams / Thinking Clients presents a postmodern look at team work that stresses working with professional knowledge in an organized context.